3D Spatial Visualisation Skills Training Application for School Students Using Hologram Pyramid - Rose Khairunnisa Roslan; Azlina Ahmad (JOIV : International Journal on Informatics Visualization, 2017)
Students need good visualisation skills to perform well in the field of Science, Technology, Engineering and Mathematics (STEM). However, two preliminary studies conducted with six teachers and fifty (50) Year 4 students at a local school showed that most of them are facing difficulties in visualizing 3D objects. From these findings and review of literature, we proposed a conceptual model called 3D Spatial Visual Skills Training (3D SVST) model. The 3D SVST model was applied as a basis to develop an application to improve 3D visualisation skills among elementary school students using a floating image technology known as hologram pyramid. In this paper, we report the findings from evaluation of students’ performance in visualisation skills test using 3D SVST application. Fifty (50) Year 4 students from a local school in the state of Selangor participated in the study. Two types of tests were conducted on students; 3D visualisation skills test using paper and 3D visualisation skills test using hologram pyramid. The tests include Paper Folding Task (PFT), Mental Rotating Task (MRT) and Virtual Building Component (VBC). The results show that students’ visualisation skills improved when using the hologram pyramid application. The study also found that students performed better in PFT but lower in MRT and VBC. From the findings, we can conclude that hologram pyramid has a positive impact on visualisation skills of students. Therefore, it has the potential to be used in classroom to complement other teaching and learning materials